Transendothelial electrical resistance measurement by a microfluidic device for functional study of endothelial barriers in inflammatory bowel disease - Li, Ya; Xu, Min; Zhu, Zhu; Xu, Feng; Chen, Bing (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Inflammatory bowel disease (IBD) is a chronic relapsing and remitting disease with a rising incidence globally. Circulating exosomes play great roles in IBD pathogenesis through exosomal cargoes, especially impacting the function of endothelial barriers. Transendothelial electrical resistance (TEER) measurement is a widely used non-invasive and label-free strategy to monitor endothelial barrier function in vitro. This study established a well-designed microfluidic device to monitor the TEER changes of endothelial cellular barrier on-chip after treated with exosome derived from IBD serum. Methods: The chip comprised two layers of microfluidic chambers with top layer for the perfusion of medium to maintain the nutrition and pressure during cell culture, and bottom layer for the extracellular matrix mimic using hydrogel, which are separated by a semipermeable membrane that permitted the formation of endothelial cell barrier. Four electrodes independent from the outlets were integrated to the chip for TEER detection. In vivo mouse models mouse models and proteome profiling were performed to finding relevant regulators. Results: With this platform, significant decrease of TEER was detected, indicating that IBD serum exosome impact the endothelial cellular barrier on-chip. In vivo mouse models, IBD serum exosome treated group showed great higher DAI scores, shorter colons, more severe histological features, and higher levers of S100A8 expression, promoting the disease progress. Proteome profiling showed that TFRC and ANXA5 have great potentials as novel regulators in IBD. Discussion: This in-house customized microfluidic chip emulates the endothelial barrier microenvironment and enables the TEER monitoring, and can be used to investigate endothelial barrier function in vitro. IBD serum exosome promote the severity of disease.